What is the rest of the problem? I can help you!
Part 1)
we have
------> equation A
------> equation B
Multiply by
the equation A
------> equation C
Multiply by
the equation B
![3*(7x-5y)=-11*3](https://tex.z-dn.net/?f=3%2A%287x-5y%29%3D-11%2A3)
-------> equation D
Adds equation C and equation D
![-21x+42y=-21 \\21x-15y=-33\\---------- \\ 42y-15y=-21-33\\27y=-54 \\ y=-2](https://tex.z-dn.net/?f=-21x%2B42y%3D-21%20%5C%5C21x-15y%3D-33%5C%5C----------%20%5C%5C%2042y-15y%3D-21-33%5C%5C27y%3D-54%20%5C%5C%20y%3D-2)
therefore
<u>the answer Part 1) is the option A </u>
![y=-2](https://tex.z-dn.net/?f=y%3D-2)
Part 2)
we have
------> equation A
![6x+2y=8](https://tex.z-dn.net/?f=6x%2B2y%3D8)
Simplify Divide by
both sides
![3x+y=4](https://tex.z-dn.net/?f=3x%2By%3D4)
------> equation B
the lines A and B are parallel lines, because the slope m is equal
so
The system has no solution
therefore
<u>the answer Part 2) is the option D</u>
There is no x value as there is no solution to the system.
Part 3)
we have
------> equation A
![x-y=3](https://tex.z-dn.net/?f=x-y%3D3)
------> equation B
substitute equation B in equation A
![4x+2[x-3]=6](https://tex.z-dn.net/?f=4x%2B2%5Bx-3%5D%3D6)
![6x-6=6](https://tex.z-dn.net/?f=6x-6%3D6)
![6x=12](https://tex.z-dn.net/?f=6x%3D12)
![x=2](https://tex.z-dn.net/?f=x%3D2)
therefore
<u>the answer part 3) is the option D</u>
![x=2](https://tex.z-dn.net/?f=x%3D2)
Part 4)
Let
x---------> The number of one-step equations
y---------> The number of two-step equations
we know that
![x+y=1,120](https://tex.z-dn.net/?f=x%2By%3D1%2C120)
-------> equation A
------> equation B
substitute equation A in equation B
![3[1,120-y]-2y=1,300](https://tex.z-dn.net/?f=3%5B1%2C120-y%5D-2y%3D1%2C300)
![3,360-5y=1,300](https://tex.z-dn.net/?f=3%2C360-5y%3D1%2C300)
![5y=3,360-1,300](https://tex.z-dn.net/?f=5y%3D3%2C360-1%2C300)
![5y=2,060](https://tex.z-dn.net/?f=5y%3D2%2C060)
![y=412](https://tex.z-dn.net/?f=y%3D412)
therefore
<u>the answer part 4) is the option D</u>
![y=412](https://tex.z-dn.net/?f=y%3D412)
Answer:
![A=\$14,555.17](https://tex.z-dn.net/?f=A%3D%5C%2414%2C555.17)
Step-by-step explanation:
we know that
The compound interest formula is equal to
where
A is the Final Investment Value
P is the Principal amount of money to be invested
r is the rate of interest in decimal
t is Number of Time Periods
n is the number of times interest is compounded per year
in this problem we have
substitute in the formula above
![A=\$14,555.17](https://tex.z-dn.net/?f=A%3D%5C%2414%2C555.17)
Answer:
This relation represent y as a function of x, because each value of x is associated with a single value of y
Step-by-step explanation:
we know that
A function is a relation from a set of inputs (x values) to a set of possible outputs (y values) where each input is related to exactly one output
we have the relation
![(3, 4), (4, 3), (6, 3), (7, 8), (5, 4)](https://tex.z-dn.net/?f=%283%2C%204%29%2C%20%284%2C%203%29%2C%20%286%2C%203%29%2C%20%287%2C%208%29%2C%20%285%2C%204%29)
This relation represent y as a function of x, because each value of x is associated with a single value of y
Answer:
6abx-3bx-4ay+2by
Step-by-step explanation: